Production of Napoli salami from some swine autochthonous genetic types. II. Sensory evaluation - Zullo A.; Genovino G.; Diaferia C.; Palazzo M.; Matassino D. (Tradition and innovation in Mediterranean pig production, 2000)
The research was carried out on 'Napoli' salami obtained using separated meat, excluding neck and ham, from castrated males and whole females belonging to Calabrese, Cinta senese and Siciliano autochthonous genetic types (AGT). The sensory characteristics were judged by a tasting panel on slices of salami seasoned in two different plants for 45 d and subsequently stored for 45 and 135 d partly in a vacuum and partly under kidney fat. The results showed that genetic type, sex, conservation time and method as well as taster are critical factors for sensory characteristics. On average: (i) salami from Cinta senese is more acceptable than that obtained from the other two AGTs due to its close texture, lower rancidity, lighter meat ; (ii) in comparison with castrated males, females provide meat characterized by a closer texture, less sharp taste ; (iii) salami seasoned in the Morcone plant was judged better than that from Angri (P less than 0.001); (iv) the better overall judgement was assigned to salami at the end of seasoning (45 d).
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)